Software Module for Personal Diagnostics of Motor Functions After Stroke - Vovk, М.І.; Kutsyak, О.А. (Кибернетика и вычислительная техника, 2019)
The purpose of the paper is to develop a specialized module for the personal diagnostics of motor functions in patients after stroke, which software implements the determination of the degree of motor functions disorders and the results of their recovery using the technique for quantitative assessment of motor functions deficit. Results. The structural and functional model of the software module for personal diagnostics of motor functions and the effectiveness of their recovery as a result of rehabilitation measures in patients after stroke has been developed. Мета статті — розробити спеціалізований модуль персонального діагностування рухових функцій у хворих після інсульту, який програмно реалізує визначення ступеня порушень рухових функцій і результатів їхнього відновлення за новою методикою персонального кількісного оцінювання дефіциту рухових функцій. Результати. Розроблено структурно-функціональну модель програмного модуля персональної діагностики рухових функцій і ефективності їхнього відновлення внаслідок реабілітаційних заходів у хворих після інсульту. Цель статьи — разработать специализированный модуль персонального диагностирования двигательных функций у больных после инсульта, который программно реализует определение степени нарушений двигательных функций и результатов их восстановления по новой методике персональной количественной оценки дефицита двигательных функций. Результаты. Разработана структурно-функциональная модель программного модуля персональной диагностики двигательных функций и эффективности их восстановления в результате реабилитационных мероприятий у больных после инсульта.